A critical examination of the underlying causes of the gender gap in STEM and the influence of computational thinking projects applied in secondary school on STEM Higher Education - González-Gallego, Sofía; Hernández-Pérez, Mariana; Alonso-Sánchez, José A.; Hernández-Castellano, Pedro M.; Quevedo-Gutiérrez, Eduardo G. (Frontiers in Education, 2025)
Students’ interest in studying STEM disciplines in Higher Education has decreased over the past decades, especially among women, who have traditionally gravitated toward careers related to social sciences, education, or health—sectors more commonly associated with caregiving. To counteract this trend and prepare students for a society where STEM skills are increasingly valued and in demand, many countries have implemented educational policies that promote these skills through the development of computational thinking. Spain has joined these efforts, and the recent LOMLOE educational law includes computational thinking as a key competence to be developed, encouraging and promoting projects. However, these initiatives do not follow a unified structure but are instead adapted to the technologies and projects most accessible to students and the capacities of each educational center. This study aims to highlight the gender gap in interest toward STEM careers based on a sample of students from the Canary Islands, analyzing the factors contributing to this disparity. Additionally, it explores the role of computational thinking projects in secondary education, evaluating whether they might influence students’ interests and, consequently, help reduce the gender gap in STEM vocations and increase students’ interest in pursuing STEM Higher Education studies.